Genome-wide association studies in lettuce reveal the interplay of seed age, color, and germination under high temperatures - Sookyung Oh; Ezekiel Ahn; Ainong Shi; Beiquan Mou; Sunchung Park (Scientific Reports)
Abstract Thermoinhibition, the suppression of seed germination by high temperatures, is an adaptive trait that ensures successful seedling establishment in natural environments. While beneficial for wild plants, thermoinhibition can adversely affect crop yields due to uneven and reduced germination rates, particularly in the face of climate change. To understand the genetic basis of thermoinhibition, we conducted a comprehensive genetic analysis of a diverse panel of Lactuca spp. accessions. Our findings revealed that L. serriola, a wild ancestor of cultivated lettuce, showed relaxed thermoinhibition response compared to cultivated lettuce, suggesting that this trait may have been positively selected during early domestication in the Mediterranean region with hot, dry summers. Additionally, we found that thermoinhibition intensified with seed age but was less pronounced in dark-colored seeds, which showed increased germination under high temperatures. Genome-wide association studies identified genomic regions associated with thermoinhibition, including genes involved in ethylene and ABA signaling. Interestingly, some of these regions were also linked to seed color, suggesting a potential genetic coupling between black seed color and reduced thermoinhibition. These results highlighted the complex interplay between thermoinhibition, seed color, and domestication in lettuce, indicating a complicated nature of thermoinhibition regulation. By elucidating the genetic architecture of thermoinhibition, our study provides a valuable foundation for breeding strategies to enhance lettuce resilience to climate change.